A comparison of lip prints between Aryans-Dravidians and Mongols - Prathibha Prasad; Vanishree (Indian Journal of Dental Research, 2011)
Context: Lip prints are very useful in forensic investigation and personal identification. Like finger prints, even lip prints can be instrumental in identifying a person positively. Aims: Indians are closer to Mongoloids than to Caucasoids or Negroids as indicated by the phylogenetic tree. Most of the studies on lip prints are done in their own population. We have compared lip prints of Manipuris with other Indians (Aryans and Dravidians) who are both close to Mongoloid race and are genetically similar. Materials and Methods: A total of 100 students 50 males and 50 females were selected of whom 30 males and 30 females were of Aryan and Dravidian features and 20 males and 20 females showed the Mongol features. Study materials used were Red colored lipstick, Lip brush, Cellophane tape, White chart paper and Magnifying lens. The lip prints were analyzed by dividing them into eight compartments. Results: Analysis of lip prints showed that the most common and the least common pattern in both males and females (Aryans-Dravidians and Mongols) were the same, but the compartment wise distribution of the lip patterns was different. Conclusion: In the present study, it is established that there is no similarity of lip prints from one individual to another individual and between males and females. Regarding the comparison with Mongols, more studies with a larger sample size is necessary.